Institutional reforms in Indian irrigation - Gulati, Ashok; Meinzen-Dick, Ruth S.; Raju, K. Vengama (SAGE Publications, 2005)
As water resources become increasing scare in India and demand only increases, the challenge of sustaining irrigation systems and the lands they serve is a matter of crucial importance. In particular, the livelihood of millions of farmers is threatened. India’s canal irrigation systems, which have so far made an enormous contribution to food security, are now in crisis because of increasing competition for water, poor management, and declining funding. The authors of this book examine the nature of large-scale surface irrigation systems in India, analyze their associated problems, and discuss the options for reform. They also assess the impact of several pilot reform projects. Among the other important issues discussed are: (1) the government’s financial constraints and the political implications of farmers’ demands; (2) viable options for institutional reform, including financially autonomous irrigation agencies and incentives for increasing farmers’ participation in management; and (3) the cost of irrigation development and the effectiveness of participatory irrigation management.